Studi Morfologi, Ontogeni, Dan Strategi Reproduksi Pada Melanoides Tuberculata (Müller , 1774) Dan Stenomelania Punctata (Lamarck, 1822) (Gastropoda: Cerithioidea: Thiaridae) - Nur Rohmatin Isnaningsih; Ristiyanti M. Marwoto; Alfiah Alfiah; Riena Prihandini; Pramono H. Santoso (BERITA BIOLOGI, 2021)
The freshwater Melanoides tuberculata (Thiarid) has wide distribution and have many variation in color, size, and scluptured of their shells. Comparing with another Thiarid so called Stenomelania punctata, shell of M. tuberculata similar in having turreted shape, blackish color, number of whorls, and size of the shells. This study aim to compare more detailed between M. tuberculata and S. punctata based on their morphology, ontogeny and type of reproduction. Ontogeny studies of these two species show that M. tuberculata produces juveniles in embryonic shell form during their reproduction. This embryonic shell is nourished and developed in the subhaemocoelic brood-pouch organ as evidenced by being found in the size range 0.12–5.95 mm. One individu M. tuberculata can produce 1–66 embryonic shells. Meanwhile, in subhaemocoelic brood-pouch of S. punctata only the unshell embryo was seen and embryonic shell was not found. The difference of reproduction system determines the reproductive strategy in both species. M. tuberculata conduct euviviparity reproduction whereas S. punctata is ovoviviparous that releases juveniles in free-swimming veliger form.